A biodegradable in situ Zn–Mg2Ge composite for bone-implant applications. (1st July 2022) - Tong, Xian; Wang, Hongning; Zhu, Li; Han, Yue; Wang, Kun; Li, Yuncang; Ma, Jianfeng; Lin, Jixing; Wen, Cuie; Huang, Shengbin
Abstract: Zinc (Zn)-based composites have received extensive attention as promising biodegradable materials due to their unique combination of moderate biodegradability, biocompatibility, and functionality. Nevertheless, the low mechanical strength of as-cast Zn-based composites impedes their practical clinical application. Here we reported the mechanical properties, corrosion behavior, wear properties, and cytotoxicity of in situ synthesized biodegradable Zn–xMg2 Ge ( x = 1, 3, and 5 wt.%) composites for bone-implant applications. The mechanical properties of Zn–xMg2 Ge composites were effectively improved by alloying and hot-rolling due to particle reinforcement of the Mg2 Ge intermetallic phase and dynamic recrystallization. The hot-rolled (HR) Zn–3Mg2 Ge composite exhibited the best mechanical properties, including a yield strength of 162.3 MPa, an ultimate tensile strength of 264.3 MPa, an elongation of 10.9%, and a Brinell hardness of 83.9 HB. With an increase in Mg2 Ge content, the corrosion and degradation rates of the HR Zn–xMg2 Ge composites gradually increased, while their wear rate decreased and then increased in Hanks' solution. The diluted extract (12.5% concentration) of the HR Zn–3Mg2 Ge composite showed the highest cell viability compared to the other HR composites and their as-cast pure Zn counterparts. Overall, the HR Zn–3Mg2 Ge composite can be considered a promising biodegradable Zn-based composite for bone-implant applications. Statement of significance: This paper reports the mechanical properties, corrosion behavior, wear properties, and cytotoxicity of in situ synthesized biodegradable Zn–xMg2 Ge ( x = 1, 3, and 5 wt.%) composites for bone-implant applications. Our findings demonstrated that the mechanical properties of Zn–xMg2 Ge composites were effectively improved by alloying and hot-rolling due to Mg2 Ge particle reinforcement and dynamic recrystallization. The hot-rolled Zn–3Mg2 Ge composite showed superior cytocompatibility, satisfying corrosion and degradation rates, and the best mechanical properties including a yield strength of 162.3 MPa, an ultimate tensile strength of 264.3 MPa, and an elongation of 10.9%. Graphical abstract: Image, graphical abstract